Secular changes in late-life cognition and well-being: Towards a long bright future with a short brisk ending? - Denis Gerstorf; Gizem Hülür; Johanna Drewelies; Peter Eibich; Sandra Duezel; Ilja Demuth; Paolo Ghisletta; Elisabeth Steinhagen-Thiessen; Gert G. Wagner; Ulman Lindenberger (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
How socio-cultural contexts shape individual functioning is of prime interest for psychological inquiry. Secular increases favoring later-born cohorts in fluid intelligence measures are widely documented for young adults. In the current study, we quantify such trends in old age using data from highly comparable participants living in a narrowly defined geographical area and examine whether these trends generalize to quality of life indicators. To do so, we compared data obtained 20 years apart in the Berlin Aging Study (in 1990 - 93) and the Berlin Aging Study II (in 2013 - 14), applied a case-matched control design (per cohort, n = 161, Mage = 75), quantified sample selection using a nationally representative sample as the reference, and controlled for number of physical diseases. The later cohort performed better on the fluid intelligence measure (d = .85) and reported higher morale, less negative affect, and more positive affect (ds > .39) than the earlier cohort. We conclude that secular advances have resulted in better cognitive performance and perceived quality of life among older adults and discuss when and how advantages of later cohorts reach their limits.
Keywords: 330; cohort; cognitive ability; well-being; sociocultural factors; individual differences